Framed slant helices in Euclidean 3-space - Osman Zeki Okuyucu (SpringerOpen, 2021)
Abstract In this paper, we define framed slant helices and give a necessary and sufficient condition for them in three-dimensional Euclidean space. Then, we introduce the spherical images of a framed curve. Also, we examine the relations between a framed slant helix and its spherical images. Moreover, we give an example of a framed slant helix and its spherical images with figures.